Rage within - Roberts, Jeyn (Simon & Schuster Books for Young Readers, 2012)
After the apocalypse wipes out most of the world's population and unleashes an ancient evil, murderous Baggers begin to create a new world order and teenagers Aries, Clementine, Mason and Michael must learn how to trust and rely on each other in order to survive.